STRATEGI PENGEMBANGAN DESA SEKITAR CANDI BOROBUDUR BERDASARKAN TIPOLOGI POTENSI KEPARIWISATAAN - Akbar Preambudi (Sustainable, Planning and Culture (SPACE) : Jurnal Perencanaan Wilayah dan Kota, 2019)
The villages around Borobudur Temple have many tourism potentials that feel drowned by all the attention devoted to Borobudur Temple. Management of Borobudur temple with excessive business systems resulted in prosperity or poverty problems experienced by the people in the villages around Borobudur. In relation with the determination of the development potential model for tourism, then this study adopts the dynamics of tourism development proposed by Miossec (Pearce 1989). Evolutionary model is based on four factors that may affect the development, namely; (1) resort; (2) transport; (3) tourist behavior; (4) attitudes of decision makers and population of receiving region. Factors that affect the â€œresort aspectsâ€ are the existence of recreation facilities and geographical location in the plains. Factors that affect the â€œtransport aspectsâ€ are the existence of many modes of transportation and impassable by public transport routes. Factors that affect the â€œtourist behavior aspectâ€ are the charter travelers type and leisure travelers type. Factors that affect the aspect of â€œattitudes of decision makers and population of receiving regionâ€ are the antagonism behavior of the public and the local officials that are less supportive of tourism.